2004
DOI: 10.1007/s11746-004-0895-6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of BSA on antioxidant activities in model food emulsions

Abstract: Sunflower oil-in-water emulsions containing TBHQ, caffeic acid, epigallocatechin gallate (EGCG), or 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox), both with and without BSA, were stored at 50 and 30°C. Oxidation of the oil was monitored by determination of the PV, conjugated diene content, and hexanal formation. Emulsions containing EGCG, caffeic acid, and, to a lesser extent, Trolox were much more stable during storage in the presence of BSA than in its absence even though BSA itself did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 15 publications
8
40
0
Order By: Relevance
“…Therefore, gelatin modified with oxidised tannic acid had the ability to retard TBARS formation in the oil-in-water emulsion system. This result was in agreement with Almajano and Gordon (2004) who reported that interaction of BSA and epigallocatechin gallate (EGCG) could induce the formation of a BSA-antioxidant adduct and cause a synergistic increase in the oxidative stability of sunflower oil-in-water emulsion effectively, when compared with BSA or EGCG alone.…”
Section: Changes In Lipid Oxidation Of Emulsion During Storagesupporting
confidence: 92%
“…Therefore, gelatin modified with oxidised tannic acid had the ability to retard TBARS formation in the oil-in-water emulsion system. This result was in agreement with Almajano and Gordon (2004) who reported that interaction of BSA and epigallocatechin gallate (EGCG) could induce the formation of a BSA-antioxidant adduct and cause a synergistic increase in the oxidative stability of sunflower oil-in-water emulsion effectively, when compared with BSA or EGCG alone.…”
Section: Changes In Lipid Oxidation Of Emulsion During Storagesupporting
confidence: 92%
“…Certain proteins at pH values below their pI can form positively charged emulsion droplets that are less susceptible to metal-promoted oxidation. 3 Although, it is well known that oxidation is accelerated as temperature increases, 4 there are limited published data on temperature dependence of oxidation rate in oil-in-water emulsions, which concern mostly subzero or low temperatures. 5,6 A body of recent research 7,8 has focused on homogenized, protein-stabilized oil-in-water emulsions, by elucidating their susceptibility at temperature-related microstructural irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…11 A synergistic effect of bovine serum albumin with phenolic antioxidants was recently proposed as the main mechanism of inhibition against the oxidative deterioration of food emulsions. 12 However, a better knowledge of the factors that determine the development of lipid oxidation in emulsions where proteins constitute the stabilizing interface can lead to their optimized use as food ingredients. 13 This research work initially focuses on the effect of several compositional parameters (such as type and content of protein and lipid phase) against the lipid autoxidation of simple model oil-in-water emulsions.…”
Section: Introductionmentioning
confidence: 99%